2000
DOI: 10.1007/s002440010098
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of DDT and Metabolites from Fruit Orchard Soils to American Robins ( Turdus migratorius ) Twenty Years After Agricultural Use of DDT in Canada

Abstract: Wildlife contamination studies found high levels of DDT and associated metabolites in bird eggs from Canadian orchard sites during the early 1990s. The present study investigated local dietary uptake of DDT and geographic variability in tissue concentrations in the same orchards. A soil-earthworm-robin food chain was chosen for study, as early surveys showed that robins contained the highest levels of DDT of several avian species and because published research indicated that earthworms were a probable dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 39 publications
5
62
2
Order By: Relevance
“…Concentration factors measured in recent studies are in the same range. As part of a study examining the bioaccumulation of DDE in robins inhabiting orchards in Canada, Harris et al (2000) reported average DDE concentration factors (dry weight) of 3.77-5.21 at their three sites. Earthworms from parks in Beijing, China, had a median DDT (sum of all compounds) concentration factor (dry weight) of 7.47 (Li et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration factors measured in recent studies are in the same range. As part of a study examining the bioaccumulation of DDE in robins inhabiting orchards in Canada, Harris et al (2000) reported average DDE concentration factors (dry weight) of 3.77-5.21 at their three sites. Earthworms from parks in Beijing, China, had a median DDT (sum of all compounds) concentration factor (dry weight) of 7.47 (Li et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Both of these topics are useful to risk assessors. Although most uses of these insecticides were cancelled in the 1970s, they remain biologically available to wild birds over widespread areas (Harris et al 2000) and are still the cause of fish advisories (New Department of Health 2012). They were the contaminants of concern at a minimum of 312 active EPA superfund sites 49 in 2011 (Search Superfund Site Information 2012).…”
Section: Introductionmentioning
confidence: 99%
“…6) showed that highest DDT/DDE ratios for the shallow subsurface soils and deep layer soils were located at the southwest and southeast sites, respectively, where high DDTs levels were found. Extremely high ratios were found in the deep layer soils, probably because of the long-term leaching of p,p 0 -DDT and retarded degradation of DDT to DDE in the deep layer soils (Miglioranza et al, 1999;Harris et al, 2000). Great proportions of p,p 0 -DDT were also observed in agricultural soils of central Germany (Manz et al, 2001) and of southern Ontario (Meijer et al, 2003), and in some western USA soils (Hitch and Day, 1992).…”
Section: Compositions Of Oc Residuesmentioning
confidence: 99%
“…The origin and fate of OCPs in soils with different land use have been extensively studied in many countries. Although the usage of OCPs was phased out for decades, the elevated concentrations were still observed in many agricultural soils (Szeto and Price, 1991;Harris et al, 2000) and the relationship between sites of greatest application and current residue levels was found strong (Shivaramaiah et al, 2002). The release of OCPs from soils continues to be a source to the environment (Munn and Gruber, 1997;Meijer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although concentrations of organochlorine compounds (OCs) in birds from most of the United States and Canada have decreased over the last 30 years, there is still concern that migrant birds might be exposed to elevated concentrations of persistent organochlorine pollutants (POPs) in Latin America. DDT [1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane] was banned in the United States in 1972 and shortly thereafter in Canada (Harris et al 2000). Agricultural use of DDT in Mexico was discontinued around 1978(Fertilizantes Mexicanos 1981; however, DDT use for malaria control and other public health campaigns continued until around 2000 (Chanon et al 2003;http://www.cofepris.gob.mx/bv/libros.htm, December 4, 2006).…”
mentioning
confidence: 99%